Immigration and the Family - Borjas, George J.; Bronars, Stephen G. (Journal of Labor Economics, 1991)
This article studies the role of the family in determining the skill composition and labor market experiences of immigrants in the United States. Our theoretical framework, based on the assumption that family migration decisions maximize household income, shows that the family attenuates the selection characterizing the skills of the immigrant population. The empirical analysis uses the 1970 and 1980 Public Use Samples of the U.S. census and reveals that an immigrant's skills and labor market performance are greatly influenced by the composition of the household at the time of migration and by his placement in the immigration chain.